2023
DOI: 10.1002/ente.202300203
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Methanol Reforming Parameters for Enhanced Hydrogen Selectivity in an Aspen Hysys Simulator using Response Surface Methodology

Abstract: Hydrogen is the prominent fuel for a nation's industrial and infrastructural development. Hydrogen fuel fulfills the energy requirement and reduces environmental pollution concerns. Hence, every country is looking for efficient and greener hydrogen production technologies. Herein, a simulation model of a methanol‐water (as feed) reformer is developed, and the effects of reaction temperature (RT), reactor pressure (RP), and methanol‐to‐water (M‐to‐W) ratio are investigated. In contrast, the optimal conditions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…While these numbers are favorable, temperatures of 120 and 246 °C are relatively low for PdZn catalysts. Conversely, two other modeling studies predicted optimal temperatures of 328 °C at 2.6 atm and 300–350 °C at 1 atm, Figure e, over Ni/Al 2 O 3 and CuZn/Al 2 O 3 , respectively, achieving >90% methanol conversion. , …”
Section: Co Suppressionmentioning
confidence: 87%
See 2 more Smart Citations
“…While these numbers are favorable, temperatures of 120 and 246 °C are relatively low for PdZn catalysts. Conversely, two other modeling studies predicted optimal temperatures of 328 °C at 2.6 atm and 300–350 °C at 1 atm, Figure e, over Ni/Al 2 O 3 and CuZn/Al 2 O 3 , respectively, achieving >90% methanol conversion. , …”
Section: Co Suppressionmentioning
confidence: 87%
“…Elevating reaction pressure has been reported to reduce the suppression of CO, although its impact is not as significant as temperature (Figure f). , , However, some studies reported the contrary, leaving pressure open for further future investigations . Perhaps the argument applying Le Chatelier’s principle may be used for increased CO selectivity with pressure, considering the higher probability of RWGS occurrence at high pressure, especially over RWGS active catalysts like small PdZn alloy particles .…”
Section: Co Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RSM optimizes the statistical data and mathematical models. A DoE was generated by using central composite design (CCD) in Design Expert software [22,23]. The input parameters taken to generate the DoE were PTT, F/W, and HRT.…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…A design with six central points, six axial points, and eight factorial points that uses a quadratic equation [Eq. ( 1)] for data analysis was created [22]. The response R was either hydrogen (or biohydrogen) or methane in percent and the subscript a denotes the type of feed (SB, RS, or SD).…”
Section: Response Surface Methodologymentioning
confidence: 99%